Sustained Virologic Response of Patients Hospitalized Compared With Those Not Hospitalized During Treatment for Hepatitis C Virus With Direct-Acting Antivirals. Issue 5 (May 2021) - Gentene, Anthony J.; Bell, Allison M.; Pence, Alicia; Thomas, Kelly; Jakubecz, Collin; Stacy, Elizabeth; Woolf, Brittany; Guido, Maria Rose; Mueller, Eric W.; Sherman, Kenneth E.
Background: Direct-acting antivirals (DAAs) for treatment of hepatitis C virus (HCV) have resulted in great success through high attainment of sustained virologic response (SVR). Risk factors for DAA treatment failure are important to identify because of worsened outcomes with failure and high treatment cost. Objective: We sought to identify whether hospitalization during treatment affects SVR. The primary outcome was the difference in SVR at 12 weeks after treatment Methods: This multicenter, single health system retrospective cohort review compared achievement of SVR between patients hospitalized during DAA treatment for HCV with those not hospitalized during treatment. Results: Patients in the hospitalized cohort (n = 94) had more severe disease at baseline than nonhospitalized patients (n = 167) as indicated through higher Model for End-Stage Liver Disease (MELD) scores, Fibrosis-4 scores, and imaging-suggested or biopsy-confirmed cirrhosis. Patients hospitalized during treatment had lower SVR rates compared with those not hospitalized (87.2% vs 95.2%; P = 0.043) but failed to reach significance when inpatient mortality was excluded on secondary analysis (91.1% vs 95.2%; P = 0.195). Patients who were hospitalized and did not achieve SVR had higher MELD scores, were more likely to have intensive care unit stay, and had longer hospital stay compared with those who achieved SVR. Of 94 patients, 93 provided home supply of DAAs during hospitalization. Conclusion and Relevance: Patients hospitalized during DAA treatment for HCV had reduced rates of SVR. This reduced SVR rate may be driven by inpatient mortality and severity of liver disease. Patient education to bring home supply of medication for use during admission is an effective intervention.